Anti-Inflammatory Activity of an Indole Alkaloid Isolated from Bebuas (Premna serratifolia) - Muhaimin Muhaimin; Muhammad Irhash Shalihin; Madyawati Latief (The Journal of Pure and Applied Chemistry Research, 2021)
Premna serratifolia known as bebuas has long been used by Malay comunity for both food and traditional medicine. The most notable advantage of this plant is to heal woman after childbirth and to raise the notion that contains anti-inflammatory bioactive compounds. In this study, the hexane extract of bebuas was only contained steroids. Meanwhile the ethanol extract contained various secondary metabolites such as phenolics, alkaloids, flavonoids, steroids and saponins. The ethanol extract was further separated since the targeted compound isolate was an alkaloid. The isolate obtained was a yellow crystal which transformed to yellow oil after being exposed to air. The anti-inflammatory evaluation of the compound gave a result with a strong activity with ED50 = 4.06 mg/KgBW. Characterization by UV-Vis and FT-IR showed that the isolate’s spectra pattern had similarities with bufotenine. It revealed that the isolate shared the same basic skeleton with the bufotenine, especially the indole skeleton. Furthermore, it also shared the same physical form with bufotenine. These evidences strengthened the assumption that the isolate was an indole alkaloid.